Theoretical studies of carbon nanotubes interacting with magnetic atoms - Kirwan, David (Trinity College (Dublin, Ireland). School of Physics, 2009)
The past twenty years have seen an enormous increase in interest in the properties of low dimensional systems. Carbon nanotubes are an example of one such system. They possess remarkable physical properties which it is hoped could be exploited in a variety of applications. One of the more novel of these lies in the nascent field of spintronics, wherein the superlative electronic properties of nanotubes would be utilised within a magnetic environment. Motivated by these factors, the thesis presents a theoretical study of the properties of nanotubes interacting with randomly distributed transition metal atoms. This is an attempt to replicate the real physical situation in which magnetic catalyst particles, left over from the formation of nanotubes, often remain adsorbed on the surface or occupying defect sites within the tube.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin.